EMBRYONIC AND LARVAL DEVELOPMENT OF SILVER BARB (BARBODES GONIONOTUS) IN A MOBILE HATCHERY UNDER LABORATORY CONDITION - Basak, Siddhwartha Kumar; Basak, Biplop; Gupta, Nipa; Haque, Mohammad Mahfujul; Amin, Ruhul (European Scientific Journal, ESJ, 2014)
This investigation was carried out for 14 days to determine different developmental stages of embryo and larvae with special emphasis on time requirement for progress of the stages. For breeding of silver barb, PG was injected as an inducing agent for ovulation of eggs inside the ovary however, external stripping was applied to ejaculate the eggs. Sophisticated digital camera (Olympus C×41) connected with a laptop was used for intensive observation on the developmental stages in the close proximity of Low Cost Mobile Hatchery (LCMH). Well fertilized eggs were transformed into fry through different stages of embryonic development, hatchlings to larvae and then fry completing several morphological and physiological changes. The size of fertilized and unfertilized eggs was 0.8±0.05 and 0.7±0.05 mm, respectively. Initial 4 stages from fertilized egg to blastula was quicker being completed within 5 hrs compared to following 4 stages from gastrula to hatchling that took 9 hrs. This indicates quality hatchlings production within a limited time having an importance in hatchery management system. During the larval development stages, yolk sac was absorbed within 72 hrs indicating proper time of first external feeding. The alimentary canal and conversion of notochord to vertebra through segmentation occurred within 144 and 192 hrs respectively. However, final development of pectoral, pelvic and, caudal and dorsal fins with rays, mouth and scale formation were completed within 336 hrs after hatchling stage.